The Effect of Capital Structure and Dividend Policy on Firm Value with Profitability as an Intervening Variable (Study of Companies Listed on the LQ 45 Index on the Indonesia Stock Exchange 2014 - 2018 Period) - Lanny Tandean; Cepi Pahlevi; Ria Mardiana Yusuf (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2021)
This study aims to analyze the effect of capital structure, dividend policy on firm value in companies listed on the LQ 45 index on the Indonesia Stock Exchange with Profitability as an intervening variable. This study uses secondary data with purposive sampling method. The sample of this research is 25 companies with the amount of data observed is 125 data. The hypothesis test used in this study is Path Analysis with IBM SPSS software version 25. The results of this study indicate that (1) Partially, the capital structure and profitability variables have a direct influence, which means that they have a positive and significant effect on firm value in companies listed on the LQ 45 index on the Indonesia Stock Exchange for the 2014-2018 period. Meanwhile, the dividend policy does not have a direct and significant effect on the value of companies listed on the LQ 45 index on the Indonesia Stock Exchange for the 2014-2018 period. (2) Indirectly, the variables of capital structure and dividend policy have a significant effect on firm value through profitability as an intervening variable. Simultaneously, the variables of capital structure, dividend policy, and profitability have a significant effect on firm value.